2018
DOI: 10.1161/jaha.118.009117
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Residential Greenness and Cardiovascular Disease Risk

Abstract: Background Exposure to green vegetation has been linked to positive health, but the pathophysiological processes affected by exposure to vegetation remain unclear. To study the relationship between greenness and cardiovascular disease, we examined the association between residential greenness and biomarkers of cardiovascular injury and disease risk in susceptible individuals. Methods and Results In this cross‐sectional study of 408 individuals recruited from a preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 56 publications
3
65
1
Order By: Relevance
“… 23 Three cross-sectional studies in China, 24 The Netherlands 22 and Austria 25 reported lower odds of prevalent hypertension among people living near more green space, with the latter also finding similar results specifically for increased tree canopy within 1000 m. Only one longitudinal study of green space and incident hypertension had been previously conducted, finding no association in Australia. 23 Three studies of prevalent CVD and green space had been conducted, each finding affirmative results in The Netherlands, 22 the USA 26 and China. 24 One longitudinal study in Lithuania observed a lower risk of fatal and non-fatal CVD events among people living closer to a green space.…”
Section: Discussionmentioning
confidence: 88%
“… 23 Three cross-sectional studies in China, 24 The Netherlands 22 and Austria 25 reported lower odds of prevalent hypertension among people living near more green space, with the latter also finding similar results specifically for increased tree canopy within 1000 m. Only one longitudinal study of green space and incident hypertension had been previously conducted, finding no association in Australia. 23 Three studies of prevalent CVD and green space had been conducted, each finding affirmative results in The Netherlands, 22 the USA 26 and China. 24 One longitudinal study in Lithuania observed a lower risk of fatal and non-fatal CVD events among people living closer to a green space.…”
Section: Discussionmentioning
confidence: 88%
“…APOE ε4 allele carriage was related to higher risks of atherosclerosis. However, residential greenness was independently related to lower levels of sympathetic activation, reduced oxidative stress, and higher angiogenic capacity, which ultimately benefited atherosclerosis 31 . Additionally, residential greenness might affect cognitive function through the promoted physical activity 32 , and reduced environmental pollution 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence linked residential green spaces with cardiovascular health and cardiovascular risk factors. There is evidence that a high amount of green spaces is associated with a decrease in cardiovascular mortality [16], a lower hazard of CVD [17], a lower cardiovascular risk [18], and some cardiovascular risk factors, such as obesity [19] and high blood pressure [20]. However, there is no consistent pattern of associations with cardiovascular risk factors, especially in adults, as some studies found green spaces to be associated with a decrease in CVD risk factors while others found no associations [12,13].…”
Section: Introductionmentioning
confidence: 99%